The Use of Guidelines for the Empiric Treatment of Hospital-Acquired Pneumonia - Michael S Miletin; Charles K Chan (Canadian Respiratory Journal)
BACKGROUND: Several practice guidelines for the empirical antimicrobial treatment of hospital-acquired pneumonia (HAP) have been developed, but the acceptance and use of such guidelines are unknown.